IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA DI KAMPUNG BANJAR SEMINAI KECAMATAN DAYUN KABUPATEN SIAK TAHUN 2015 - Septian Dwiansyah; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Village Allocation Funds are funds allocated by the district / city for the village derived from the financial balance between the central and local governments received by Regency / City. Thus the Siak district government issued regulations of Regions No. 9 of 2010 on Village Fund Allocation. The purpose of this Regulation is such as to alleviate poverty and reduce inequality, improve development planning and budgeting and Improving rural incomes and rural communities through village-owned enterprises. This study aims to determine the Village Fund Allocation Policy Implementation in the village of Banjar Seminai 2015 and to determine the factors that influence the Village Fund Allocation Policy Implementation in the village of Banjar Seminai Year 2015. In theory the implementation model by Van Meter and Van Horn, there are six variables which forms the link between policy and performance, namely: the sizes of the basic and policy objectives, policy resources, communication between the organization and activities of implementers, implementing body characteristics, economic conditions, social and political, as well as the tendency executor.The method used in this research is qualitative research. With the technique performed is purposive sampling, to key informants in this study. In this study, the informant is the village headman in the village Banjar Seminai, Secretary of the village in the village Banjar Seminai, Treasurer of the Village in the village Banjar Seminai, chairman of the village in the Village Consultative Body Banjar Seminai and Society in the village of Banjar Seminai. Then analyzes the data and manage.Based on the research and discussion that researchers do in the field, it was found that the Village Fund Allocation Policy Implementation in the village of Banjar Seminai 2015 have not been implemented to the fullest. That's because the various factors that affect the implementation of this policy is difficult implemented optimally.Keywords: Implementation, Village Fund Allocation, Banjar Seminai